The role of pars plana vitrectomy in the management of fungal endogenous endophthalmitis - ÇELİKER ATABERK, HANDE (SAGE PUBLICATIONS LTD, 2020)
Purpose: To identify the causative microorganism of fungal endogenous endophthalmitis in our tertiary referral uveitis center and review the therapeutic role of pars plana vitrectomy in patients with fungal endogenous endophthalmitis. Methods: Seven eyes of six cases were identified as fungal endogenous endophthalmitis through positive cultures of ocular fluids and clinical presentations. The final anatomical and functional results were evaluated. Results: Four women (66.7%) and two men (33.3%) underwent vitrectomy. Control of infection was achieved early on in all cases. Candida (71.4%) and Aspergillus (28.6%) species were identified as causative fungi in patients with fungal endogenous endophthalmitis. Two patients were reoperated due to reinfection and retinal detachment, respectively. Visual acuity improved in six eyes (85.7%) and worsened in one eye (14.3%). At the final examination, the retina was flat in all cases. No eye developed phthisis bulbi. Conclusion: Candida species are the most common causative organisms of fungal endogenous endophthalmitis in this study. Pars plana vitrectomy in fungal endogenous endophthalmitis may enhance the treatment of infection by removing fungal elements in the vitreous and aid in diagnosis. Vitrectomy may also be an important tool in the management of vision-threatening post-infectious sequelae such as retinal detachment and reinfections.
Keywords: Endogenous endophthalmitis; fungal endophthalmitis; infectious; surgery; vitrectomy; CANDIDA-ALBICANS ENDOPHTHALMITIS; BACTERIAL ENDOPHTHALMITIS; TREATMENT OUTCOMES; CLINICAL-FEATURES; EXPERIENCE; 10-YEAR; RISK